VRIO: Static or dynamic? - Lopes da Costa, R. (2019)
During the 1980s, the principal concern of theorists in what regarded strategic management was linked to the analysis of the external environment. However, many researchers defend that considering the turbulence of today’s business environment with the technology’ advancement, the ever-changing industries and with an ever continuingly-increasing reduction in the time-frame of competitive advantage, a resource-based view has been gaining its own space regarding strategic formulation. Despite of the model’s capability, the theory has received diverse criticism during the last years, which we believe that some of these criticisms deserve to be analyzed. Therefore, the present article intends to illustrate a new theoretical basis for the analysis of the resources and capabilities in order to explain the advantages of applying a conceptual model that articulates the VRIO framework, initially developed by Barney (1991) with a new conceptual model that allow companies to perceive the dynamism of the company’s competitive advantage through the inclusion of the values, dynamic capabilities and governance concepts from the VDS acronym. The article is subdivided into six parts, the first part is referent to the theoretical exploitation of the RBV dematerialized in the creation of the VRIO model. The second part presents the main criticisms existent in the literature regarding the model and its limitations. The third, fourth and fifth parts refer to the approach in order to achieve the articulation between the VRIO model and the three additional parameters. In the sixth part, the new model will be presented and lastly, some considerations will be presented regarding this subject.